The factors that influence local fruit preferences among teenagers - Aifaa Syazwani Abdul Razak; Hendryanna Muslim; Nurul Atiqah Nor Hilmi; Amiruddin Abdul Rahman (2021)
This study was conducted to examine the factors that influence local fruit preferences among teenagers. The independent variables of this study comprised taste, texture, color and price; whereas the dependent variable in this study was local fruit preferences. This study had four objectives which is to examine the relationships of taste toward teenagers’ local fruit preferences, to examine the relationships of texture toward teenagers’ local fruit preferences, to examine the relationships of color toward teenagers’ local fruit preferences and to examine the relationships of price toward teenagers’ local fruit preferences. The quantitative research method was selected and questionnaire was used as the research instrument to collect data. Simple random sampling method was used and 384 respondents were evaluated in this study. The data was collected using Google form. The data collected is analysed by using Statistical Packages for Social Science Version 26 (SPSS Version 26) software based on descriptive statistic, reliability analysis, and correlation analysis. As for the result, all of the independent variables (taste, texture, color and price) that had been studied in this research had significant relationships towards dependent variable (local fruit preferences) among teenagers in Malaysia. Through this study it will understand the factor influence local fruit preferences among teenagers and a better understanding and knowledge regarding fruit’s taste, texture, color and price.